The European Distinction Model and its Impact on Sustainable Quality Management an Applied Study in the General Company for Electrical and Electronic Industries in Baghdad/Iraq - Mustafa Hamid Abd Nour; Aseel Ali Mezher (International Journal of Economics and Management Sciences, 2025)
The research aims to identify the impact of applying the European distinction model through nine criteria (Leadership criterion, Strategy criterion, Human Resources criterion, Resources and Partnership criterion, Operations and Services criterion, Customer Results, Employee Results, Community Results, Business Results) on sustainable quality management through its dimensions (continuous improvement, customer focus, creativity, adaptation, transparency, social responsibility). The research was applied in the General Company for Electrical and Electronic Industries in Baghdad/Iraq, which prompts the search for excellence by knowing the impact of the European distinction model on achieving sustainable quality management. The researchers relied on the descriptive analytical approach, and the study sample amounted to (197) individuals. The researchers relied on the statistical program (SPSS.v.29) and the statistical program (AMOS.v.26) to analyze the study data statistically, to help test the study hypotheses. After conducting the necessary statistical analyses and testing the study hypotheses, the study reached a set of results, the most important of which is the existence of a significant impact of applying the European distinction model on sustainable quality management.